ANATOMICAL EDUCATION IN REHABILITATION SCIENCES: CURRENT CHALLENGES AND PATHWAYS FOR IMPROVEMENT (Physical Culture and Sport: Scientific Perspective, 2025)
This article presents a comprehensive meta-analysis of the current state of anatomical education in the field of rehabilitation sciences, particularly in the training of specialists in physical therapy, occupational therapy, and sports rehabilitation. It reviews studies addressing the key challenges facing traditional approaches to teaching anatomy in the context of digitalization, interdisciplinary integration, and increasing clinical demands. The focus is on the need to adapt educational programs to the needs of the 21st century, especially through the implementation of innovative technologies (VR/AR, 3D modeling, simulation platforms), gamification strategies, blended learning, and functionally oriented methods. The study analyzes scientific sources, including empirical research, systematic reviews, and pedagogical interventions conducted between 2018 and 2025. It finds that effective anatomical training requires a combination of classical methods (dissection, anatomical atlases) and digital tools that provide interactivity, spatial visualization, and clinical relevance. Special attention is given to the role of the educator as an interdisciplinary facilitator capable of integrating anatomical knowledge into clinical contexts. The results of the meta-analysis indicate a positive impact of multimodal approaches on academic performance, motivation, critical thinking, and students’ clinical competence. At the same time, several issues are identified, including unequal access to resources, lack of pedagogical training among instructors, and the absence of standardized criteria for evaluating the effectiveness of innovative methods. In conclusion, the authors justify the need for strategic modernization of anatomical education in rehabilitation sciences based on evidence-based pedagogy, digital transformation, interdisciplinary approaches, and a focus on practical clinical skills. Promising directions for further research are proposed, including the development of integrated educational models, the study of the impact of digital technologies on clinical reasoning, and the creation of competency-based curricula.
Keywords: anatomy; physical therapy and rehabilitation; interdisciplinary integration; emerging technologies; anatomical training of learners